Penyuluhan Tentang Pemanfaatan dan Perbaikan Fisik Jamban Keluarga Di Kecamatan Selemadeg Timur Kabupaten Tabanan Tahun 2018 - Nengah Notes; I Gede Wayan Darmadi; I Wayan Sudiadnyana; I Nyoman Gede Suyasa (Jurnal Pengabmas Masyarakat Sehat, 2019)
Health degrees are influenced by several environmental factors, behavior, health services, and offspring. Environment is a factor that has a large influence on the health of individuals and society. Environmental conditions that do not meet community health and behavior requirements can be detrimental to health in both rural and urban communities. Community service aims to find out the ownership and knowledge of the head of household before and after counseling. The method is used for family heads who do not have family latrines as respondents, then interviews are conducted using questionnaires. The results of community service as many as 38 respondents answered the questionnaire preetest and posttest and repaired two family toilet units.Recapitulation of questionnaire ownership and knowledge of family latrines: pretest of toilet ownership as much as 18.4% of respondents could answer, and post-ownership of latrines as much as 81.6% of respondents could answer. Whereas 5.3% of respondents can answer the toilet pretest and 58% of respondents can answer. It is expected that residents who have improved family latrines to maintain and use latrines regularly.Keywords: Family Latrine Extension